"A Feeling of Connectedness": Perspectives on a Gentle Yoga Intervention for Women with Major Depression. (1st June 2013) - Kinser, Patricia Anne; Bourguignon, Cheryl; Taylor, Ann Gill; Steeves, Richard
<x xml:space="preserve">Abstract</x> Major depressive disorder (MDD) is one of the most common and debilitating health conditions in women in the United States and worldwide. Many women with MDD seek out complementary therapies for their depressive symptoms, either as an adjunct or alternative to the usual care. The purpose of this study is to understand the experiences of women who participated in a yoga intervention for their depression. The findings from this interpretive phenomenological study are derived from interviews with and daily logs by 12 women with MDD who took part in an 8-week gentle yoga intervention as part of a larger parent randomized, controlled trial. Results show that the women's experience of depression involved stress, ruminations, and isolation. In addition, their experiences of yoga were that it served as a self-care technique for the stress and ruminative aspects of depression and that it served as a relational technique, facilitating connectedness and shared experiences in a safe environment. Future long-term research is warranted to evaluate these concepts as potential mechanisms for the effects of yoga for depression.